From Passive Learning to Critical Thinking - نجاة احمد الجبوري (College of Education for Women, 2019)
Many Iraqi students are reluctant to actively participate in the English language classroom. This reluctance is attributed to a number of factors, above which is students' lack of thinking skills necessary to express their points of view. This eventually results in passive learning, a real problem in English language learning in Iraq. A need for educational reforms and innovations seems essential. These involve developing relevant teaching materials, adopting learner-centered approach, promoting learner autonomy, and enhancing critical thinking. This study is hoped to assist teachers of English to initiate change and foster the expansion of thinking, and adopt various new strategies to increase classroom participation. The paper also aims to enable Iraqi students to be active thinkers rather than passive attendees.